1996
DOI: 10.1093/infdis/174.5.986
|View full text |Cite
|
Sign up to set email alerts
|

The Continued Emergence of Drug-Resistant Streptococcus pneumoniae in the United States: An Update from the Centers for Disease Control and Prevention's Pneumococcal Sentinel Surveillance System

Abstract: As part of ongoing national surveillance, serotyping and antimicrobial susceptibility testing were done on all pneumococcal isolates recovered from normally sterile body sites of patients at 12 hospitals in 11 states during 1993-1994. Of 740 isolates, 14.1% were penicillin-nonsusceptible Streptococcus pneumoniae (PNSP; MIC > or = 0.1 microgram/mL), 3.2% were penicillin-resistant (MIC > or = 2.0 micrograms/mL), and 25.5% were nonsusceptible to more than one antimicrobial agent. PNSP were more prevalent among ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(171 citation statements)
references
References 45 publications
4
164
0
3
Order By: Relevance
“…6. CDC surveys are reported in Spika et al (1991), Breiman et al (1994), Butler et al (1996), andCDC (1999a;1999b). Surveys directed by the university-based researchers Gary Doern and Angela Brueggemann are reported in Doern et al (1996a;.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6. CDC surveys are reported in Spika et al (1991), Breiman et al (1994), Butler et al (1996), andCDC (1999a;1999b). Surveys directed by the university-based researchers Gary Doern and Angela Brueggemann are reported in Doern et al (1996a;.…”
Section: Resultsmentioning
confidence: 99%
“…For modeling purposes, we assume that the PRP data presented above give an accurate indication of trends in resistance by pneumococci to betalactams generally. In fact, the available evidence suggests that pneumococcal resistance to cephalosporins tends to move in parallel with resistance to penicillin (Butler et al 1996;Doern et al 1999;Fenoll et al 1998;Marton 1992;Lee et al 1995;Song et al 1999). Although the PRP data are specific to penicillin, it must be recognized that all beta-lactams, and not only penicillin, are capable of encouraging the spread of the sort of resistance genes that can inactivate penicillin.…”
Section: Data On Beta-lactam Antibiotic Usementioning
confidence: 99%
“…Approximately 10 -15% of S. pneumonia isolates are resistant to macrolides in vitro, so that caution is necessary when these agents are used empirically in suspected cases of P. pneumonia. 24 Of the three macrolides, azithromycin is most active in vitro against legionella species, H. influenzae and M. pneumoniae, whereas clarithromycin is the most active against S pneumoniae and C. pneumoniae. A recent multicenter prospective study of patients with CAP showed that use of Erythromycin is a cost effective treatment.…”
Section: Antibiotic Considerationmentioning
confidence: 99%
“…Especially troublesome is the emergence of diverse pathogens that became multi-drug resistant [4][5][6][7], posing a serious threat to global public health. During this same period, few antibiotics of New Chemical Entities (NCEs) have emerged [8], reflecting both the challenges of identifying NCEs and a reduced commitment of antibiotic drug discovery by pharmaceutical companies.…”
Section: Introductionmentioning
confidence: 99%